The first green lacewing (Insecta: Neuroptera: Chrysopidae) from the mid-Cretaceous amber of Myanmar - Lu, Xiumei; Wang, Bo; Ohl, Michael; Liu, Xingyue (Zootaxa, 2018)
The lacewing family Chrysopidae is here reported from the mid-Cretaceous amber of Myanmar for the first time. A new genus and species, Parabaisochrysa xingkei gen. et sp. nov., is described. The new genus belongs to the extinct subfamily Limaiinae and is characterized by the presence of three gradate series of crossveins in both fore- and hind wing, and by the MP1 coalescent with RP+MA in the hind wing.